Reptilia, Squamata, Dipsadidae, Pseudotomodon trigonatus (Leybold, 1873) : distribution extension - Avila, Luciano Javier (2009)
Pseudotomodon trigonatus (Leybold, 1873) is a small-sized dipsadid snake (about 450 mm total length) endemic to Argentina (Figure 1). It is the single species of the genus, and its geographic distribution ranges through the western and southern areas of Monte phytogeographic region and neighboring areas (Cei 1986; Scrocchi 1997; Avila 1997; Tiranti and Avila 1997; Avila et al. 1998; Giraudo and Scrocchi 2002). In Chubut province is known only from Puerto Madryn, in northwestern Chubut (Scolaro and Cei 1979) and from an area near Punta Tombo, about 120 km S of the previous record (Cruz et al. 1999). In a recent field guide (Scolaro 2005) the geographic distribution outlined is restrict the species to the northeast corner of Chubut Province.